Potensi Kerjasama Ekonomi dan Keamanan India–Afghanistan Paska Kemenangan Taliban Tahun 2021 - Susilowati, Ida; Fauzi, Muhammad; Hidayat, Regga Fajar; Nabeel, Thoriq (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. The internal conflict between the Afghan government and the Taliban has been going on for a long time, and in mid-August 2021 the Taliban succeeded in taking over the Afghan government in Kabul. Various countries began to respond to the event, especially countries that have established diplomatic, economic and military cooperation with Afghanistan, including India. This article aims to analyze the potential for bilateral cooperation in the economic and security fields between India and Afghanistan, especially after the Taliban's success in occupying Kabul and announcing the Afghan government under the Taliban. Qualitative research with descriptive analytical methods is applied in this research, based on data sources obtained through literature study techniques. This research shows that India has the potential to take a policy to continue to cooperate with Afghanistan in the economic and security fields. This due to India's national interest in Afghanistan such as controlling Afghanistan's mineral resources and realizing India as a regional power in the South Asian region. Keywords: National Interest, Bilateral Cooperation, India, Afghanistan, Taliban. Abstrak. Konflik internal antara pemerintah Afganistan dan Taliban telah berlangsung sejak lama, dan di pertengahan bulan Agustus 2021 Taliban berhasil mengambil alih pemerintahan Afghanistan di Kabul. Berbagai negara mulai merespon peristiwa tersebut, terutama negara-negara yang menjalin kerjasama diplomatik, ekonomi dan militer dengan Afghanistan tidak terkecuali India. Artikel ini bertujuan untuk menganalisis potensi kerjasama bilateral di bidang ekonomi dan keamanan antara India dengan Afganistan, terutama paska keberhasilan Taliban menduduki Kabul dan mengumumkan pemerintahan Afghanistan dibawah Taliban. Penelitian kualitatif dengan metode deskriptif analitis diterapkan dalam penelitian ini, berdasarkan sumber-sumber data yang diperoleh melalui teknik studi pustaka. Penelitian ini menunjukkan bahwa India berpotensi mengambil kebijakan untuk tetap bekerjasama dengan Afghanistan di bidang ekonomi dan keamanan. Hal tersebut tidak terlepas dari kepentingan nasional India terhadap Afghanistan seperti menguasai sumber daya mineral Afganistan dan mewujudkan India sebagai regional power di kawasan Asia Selatan.Kata Kunci: Kepentingan Nasional, Kerjasama Bilateral, India, Afghanistan, Taliban.